Does the integration of agriculture and tourism promote agricultural green total factor productivity?—Province-level evidence from China - Wang, Jingjing; Zhou, Faming; Chen, Chen; Luo, Zhonghua (Frontiers in Environmental Science, 2023)
The integrated development of agriculture and tourism is conducive to the realization of agricultural ecological value, which will promote the green development of agriculture and improve the green total factor productivity of agriculture as well. Based on panel data of 30 provinces in China from 2008 to 2019, the super-efficiency SBM method and the coupling coordination degree were used to estimate the agricultural green total factor productivity (AGTFP)and the integration level of agriculture and tourism(ATL). The dynamic spatial Durbin model and threshold effect model were used to demonstrate the effects and characteristics of the integrated development of agriculture and tourism on ATL. Results showed that: (1) During the study period, AGTFP and ATL increased steadily, and showed obvious spatial agglomeration characteristics; (2) The integration of agriculture and tourism will directly promote the improvement of AGTFP in the local region, but also has an impact on the improvement of AGTFP in its surrounding areas, showing a spatial spillover effect. The direct effect in the central region in China is the strongest, and the spillover effect in the eastern region is the largest. (3) The influence of the integration of agriculture and tourism on AGTFP was enhanced with the improvement of ATL, showing a threshold characteristics. From the perspective of subregion, the threshold value of ATL in the eastern region is the lowest, while the threshold value in the western region is the highest. The results of this study provide useful enlightenment for promoting the deep integration of agriculture and tourism and improvement of AGTFP so as to promote the green development of agriculture.